2015
DOI: 10.4137/bmi.s18519
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphism in Variable Number of Tandem Repeats of Dopamine D4 Gene is a Genetic Risk Factor in Attention Deficit Hyperactive Egyptian Children: Pilot Study

Abstract: INTRODUCTIONThe variable number of tandem repeats (VNTR) of the dopamine receptor D4 (DRD4) gene among humans may elucidate individual differences in susceptibility to neuropsychiatric diseases. Dopamine dysfunction may be involved with Attention Deficit Hyperactivity Disorder (ADHD) symptoms. In this study, we report the association between the phenotype of ADHD, a condition characterized by inattentiveness, hyperactivity, and impulsiveness, and a 48-base pair VNTR in exon 3 of the DRD4 polymorphism.SUBJECTS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 39 publications
2
3
0
Order By: Relevance
“…As it is seen, 4R is more prevalent in Asians than White Caucasians and Europeans [ 14 ]. High prevalence of 4R reported by Shahin et al in Egypt [ 25 ], as well as our study confirms this finding.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…As it is seen, 4R is more prevalent in Asians than White Caucasians and Europeans [ 14 ]. High prevalence of 4R reported by Shahin et al in Egypt [ 25 ], as well as our study confirms this finding.…”
Section: Discussionsupporting
confidence: 93%
“…Though these studies were in line with the present study considering 4R as an indicator of ADHD, studies on other populations, specifically White Europeans and Americans showed a greater role of 7R alleles in the development of ADHD [ 25 ]. In contrast, our study did not show any significant relationship between 7R alleles and ADHD.…”
Section: Discussionsupporting
confidence: 91%
“…The variable number of tandem repeats (VNTR) in exon 3 of the DRD4 gene has been implicated in the etiology of ADHD ( Chang et al, 1996 ; Bidwell et al, 2011 ). Interestingly, different populations have different risk alleles, for instance, the 2-repeat allele (2R) has been noticed in the Han Chinese ( Chang et al, 1996 ) and Koreans ( Hong et al, 2018 ), 4-repeat allele (4R) for Asians while 7-repeat allele (7R) for white Europeans and Americans ( Faraone et al, 1999 ; Hawi et al, 2000 ; Shahin et al, 2015 ; Tabatabaei et al, 2017 ). A haplotype of markers: allele 2 of the 120 bp duplication, 616 C/G substitutions, and 521 C/T substitutions of the C allele can confer a predisposition to ADHD ( Mill et al, 2003 ).…”
Section: Resultsmentioning
confidence: 99%
“…As shown in table 1 (model a), a significant association was observed between the DRD4 exon III VNTR and political attitude (OR ¼ 0.820, p ¼ 0.027), the 4R/4R carriers were less liberal than other subjects. Comparison of 4R/4R with all other DRD4 genotypes is not an uncommon practice [68][69][70][71][72][73]. Additionally, presence of a single 7R trumps the effect of the 4R in many studies hence it is not surprising that the 4R/4R grouping has special significance.…”
Section: Results (A) Summary Statisticsmentioning
confidence: 99%